The Influence of Plantar Short Foot Muscle Exercises on Foot Posture and Fundamental Movement Patterns in Long-Distance Runners, a Non-Randomized, Non-Blinded Clinical Trial - Sulowska, Iwona (PLoS One, 2016)
BACKGROUND: The objective of this study was to evaluate the influence of two kinds of plantar short foot muscles exercise on foot posture and fundamental movement patterns in long-distance runners. DESIGN: A parallel group non-blinded trial with 6-week follow-up. METHODS: Twenty five long-distance runners aged 22–35 years. They were divided into two groups. In group 1 (n = 13) subjects performed the exercise “Vele’s Forward Lean” and “Reverse Tandem Gait” and in Group 2 (n = 12) the “Short Foot Exercise.” The runners performed the exercises daily for 6 weeks. The Foot Posture Index (FPI-6) and The Functional Movement Screen (FMS) tests were performed twice: at baseline and after 6 weeks of the exercise. RESULTS: A significant improvement was observed in FPI -6 (talar head palpation in Group 1, and inversion/eversion of the calcaneus in Group 2). Also in Group 1 a significant improvement was noted in FMS tests: deep squat, active straight leg raise and in total score. CONCLUSIONS: Short foot muscles strengthening exercises have beneficial effect on functional movement patterns and on foot posture, therefore they should be included as a part of daily training program of runners. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12615001200572